Optimizing the delivery process by implementing fleet management with IoT at Berger Paints Bangladesh Ltd. - Fuad, Mohammad Muhtashim (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.